Relationship of Sarcopenia with Microcirculation Measured by Skin Perfusion Pressure in Patients with Type 2 Diabetes - Jung, Chan-Hee (Endocrinol Metab (Seoul), 2020)
BACKGROUND: Few studies have examined the relationship of sarcopenia with the microcirculation. The current study investigated the relationship of sarcopenia with microcirculatory function, as assessed by skin perfusion pressure (SPP), in type 2 diabetes mellitus (T2DM) patients. METHODS: In total, 102 T2DM patients who underwent SPP measurements and bioelectrical impedance analysis (BIA) were enrolled in this cross-sectional study. SPP was assessed using the laser Doppler technique. Sarcopenia was defined as low height-adjusted appendicular muscle mass (men, <7 kg/m(2); women, <5.7 kg/m(2)) using BIA. We divided the participants into two groups based on SPP (≤50 and >50 mm Hg), and an SPP below 50 mm Hg was considered to reflect impaired microcirculation. RESULTS: Fourteen patients (13.7%) were diagnosed with impaired microcirculatory function of the lower limb based on SPP. The prevalence of sarcopenia in all subjects was 11.8%, but the percentage of patients with an SPP ≤50 mm Hg who had sarcopenia was more than triple that of patients with an SPP >50 mm Hg (28.6% vs. 9.1%, P=0.036). A significant positive correlation was found between SPP and appendicular muscle mass adjusted for height (P=0.041 for right-sided SPP). Multiple logistic regression analysis showed that patients with sarcopenia had an odds ratio of 4.1 (95% confidence interval, 1.01 to 24.9) for having an SPP ≤50 mm Hg even after adjustment for confounding factors. CONCLUSION: These results suggest that sarcopenia may be significantly associated with impaired microcirculation in patients with T2DM. Nonetheless, the small number of patients and wide CI require cautious interpretation of the results.